Mechanics of biological systems, materials and other topics in experimental and applied mechanics. proceedings of the 2017 Annual Conference on Experimental and Applied Mechanics /: proceedings of the 2017 Annual Conference on Experimental and Applied Mechanics. Volume 4 : ([2018]) - Unknown
No abstract available